2018
DOI: 10.7575/aiac.ijels.v.6n.1p.86
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Language Learning Strategies and Positive Emotions among Malaysian ESL

Abstract: Emotions are an indispensable part of second language learning. The aim of this study is to determine the relationship between the use of language learning strategies and positive emotions. The present study adopted a sequential mixed methods design. The participants were 300 Malaysian ESL undergraduates selected through stratified random sampling from 5 public universities in Malaysia. The quantitative data were collected through two sets of questionnaires: (a) Oxford's (1990) Strategy Inventory for Language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In this stage, the students practice their critical thinking related to the topic. This activity gave the students chance to decrease their communicative pressure, increase their confident and at last increase their speaking ability [25]. This also helped the students to identify the speaking strategies that they can use in report stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this stage, the students practice their critical thinking related to the topic. This activity gave the students chance to decrease their communicative pressure, increase their confident and at last increase their speaking ability [25]. This also helped the students to identify the speaking strategies that they can use in report stage.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was found that intrinsic motivation helps the students to achieve better speaking proficiency [24]. It was also found that the authentic or real world tasks can intrinsically motivate students to accomplish the task and hence increase speaking skill [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that gender and personality types have some effects on pre-service teachers' strategy use at the overall, category and individual levels. Junior (Tjandra, 2021) Urban schools (Ardasheva, 2016;Rusli et al, 2019) High Schools (Fernandez-Malpartida, 2021;Babikkoi & Abdul Razak, 2014;;Liyanage & Bartlett, 2013) Senior High Schools (Sukirlan et al, 2020) Religious School (Ismail & Yusoff, 2021) Colleges (Alharbi, 2015;Chan, 2014;Huang, 2015;Hou et al, 2014 ;Yi-An, 2013) Universities / Institutions Pre-service teachers (Zhou & Intaraprasert, 2014) Adult learners of TESL (Hashim et al, 2018) English teacher of education undergraduates (Intriago et al, 2017) Non-TESL learners (Chang & Liu, 2013;Giang & Tuan, 2018;Kunasaraphan, 2015;Luo & Weil, 2014;Madhumathi et al, 2014 ;Nazri et al, 2016;Shah et al, 2013;Rianto, 2020;Sheu, Wang, & Hsu, 2013;Sukying, 2021) Undergraduate learners of English (Rahimirad & Zare-ee, 2015) Graduates of education studies (Sadeghi et al, 2021;Setiadi & Piyakun, 2019) ESL Net-Geners (Shakarami et al, 2017) Not specified (Fu et al, 2018;Danko & Decman, 2019;Kamalizad & Samuel, 2015;Kasim et al, 2019 ;Ida Rahimah et al, 2014 ;Mohammadipour ...…”
Section: Teachersmentioning
confidence: 99%
“…Most importantly, my interpretation of these findings considered the fact that learners' perceptions and their actual performance were consistent in some studies and contradictory in others (Moattarian, 2012) which encouraged researchers to highlit complexity and sensitivity of the strategic behaviour. For instance, Mohammadipour, Rashid, Rafik-Galea & Thai (2018) show that learners' positive emotions were replicated in more habitual and a variety of language learning strategies' use. Therefore, there is a difficulty in the generalisability of research findings and linking research findings to others in different contexts (Barrios, 2015).…”
Section: Discussion Of the Findings Of The Libyan Teachers And Studenmentioning
confidence: 99%